Failure analysis of a martensitic stainless steel (CA-15M) roll manufactured by centrifugal casting. Part II: Thermal stress analysis by FEA. (February 2015) - Ariza, E.A.; Tschiptschin, A.P.; Azevedo, C.R.F.
Highlights: The failure of a centrifugal cast roll by thermal stress was investigated via FEA. The stable and unstable crack growth was studied by fracture mechanics. The growth of a longitudinal crack was related to the thermal history of the roll. Abstract: A martensitic stainless steel (CA-15M) roll manufactured by centrifugal casting and used as a glass roller failed prematurely after six rolling campaigns. A previous fractographic investigation showed that the failure of the roll was caused by thermal stresses associated with microstructural embrittlement of the steel casting. Crack nucleation took place on the internal surface of the roll and the crack propagated by ductile intergranular mode. In the present work, the thermal stresses distribution was investigated by a thermal elastic–plastic model using finite element analysis in order to associate the crack growth with the thermal history of the roll during service. The proposed methodology based on the assessment of thermal stresses by finite element analysis together with coupled thermal–mechanical non-linear modelling and calculations using non-linear elastic–plastic fracture mechanics allowed a better understanding of the stable and unstable growth of a longitudinal crack until the premature failure of the roll during its cooling to room temperature after the sixth campaign. The stable and unstable crack growth and the thermal history of the roll (heating up, glass rolling and cooling operations during the six campaigns of the roll) could be related using the proposed calculation.